KOMUNIKASI TERAPEUTIK PERAWAT DALAM MENINGKATKAN MOTIVASI POLA HIDUP AKTIF DAN SEHAT PADA LANSIA KATEGORI PARSIAL GRIYA WREDA JAMBANGAN SURABAYA - Retno Dewanti, Niken Pramesthi; Tandyonomanu, Danang (The Commercium, 2024)
Therapeutic Communication is an interpersonal relationship between the counselor and client. Through this relationship, the counselor and client gain joint learning experiences in order to improve the client's emotional experience. Therapeutic communication is a type of interpersonal communication that is useful for assisting in the process of stimulating and changing behavior carried out by nurses towards patients or clients. Therapeutic communication is usually carried out to change thought patterns which can ultimately influence the patient's activities. Based on the Sustainable Development Goals which have become a world agreement and were drafted by the UN in point number 3, it states "Good Health and Prosperity" where health must be equal for all people, including paying attention to the health of the elderly. Apart from the declining function of the body's organs which can affect the health of the elderly, the elderly usually start to experience senility or easily lose their memory of certain things, and in the elderly the motivation to live a healthy and active life has begun to decline. In this research, a qualitative phenomenological research approach will be used. Based on the results of research that has been carried out regarding communication patterns that are applied as therapeutic communication by nurses to elderly people in the partial Griya Wreda Jambangan category, three communication patterns were found according to the elderly carried out by nurses to the elderly. The first is the nurse's closeness to the elderly, including inviting interaction and communication with the elderly. The second is complaints from the elderly to the nurse. After the elderly get to know the nurse, the elderly express their complaints to the nurse. And the third is the nurse's actions regarding reports or complaints from the elderly. At this stage, therapeutic communication really needs to be applied to the elderly. Apart from medical measures, nurses need to motivate the elderly with therapeutic communication so that the elderly can recover optimally.